Coach-swimmer communications based on wrist mounted 2.4ghz accelerometer sensor - Hagem, R. M.; Sabti, H. A.; Thiel, D. V. (Procedia Engineering, 2015)
Two way real time communications during swimming is important for coaches and swimmers in order to reach optimum performance. This paper presents a 2.4 GHz wireless communication system to send acceleration data to a coach tablet at the pool side and allow active interactions between swimmers and their coaches. The radio frequency signal does not propagate effectively underwater because of the high attenuation. Therefore the wireless transmitter sends data only when the swimmer's wrist is outside the water. The y-axis acceleration data provides stroke rate SR, stroke length and swim velocity. The experimental results showed that the link is operational 28% per stroke in freestyle swimming. This is more than enough to send important data from the swimmer and reply with the coach's feedback.